Nowhere to run - Bush, Nancy, 1953- (New York : Kensington Publishing Corp., 2012)
When Liv Dugan ducks out of work for lunch, it's just an ordinary day. When she returns, she stumbles onto a massacre. All her colleagues at Zuma Software have been shot. Only luck has left Liv unscathed, and that might be running out. Liv suspects the shootings are tied to her past - and to the package she recently received from her long-dead adoptive mother. Sensing she's being followed, Liv jumps into a stranger's car and orders him to drive. Her "hostage" complies, listening carefully as her story unwinds. Skeptical at first, he ultimately begins to believe all Liv's fears are justified. Together, Liv and her unlikely confidant try to uncover the truth about her adoptive family, her birth parents, and her troubled childhood. Because somewhere in Liv's past is a secret worth killing for, and a nightmare she can never outrun.
Keywords: Massacres -- Fiction; Family secrets -- Fiction; Suspense fiction; Love stories